Imagining Wild Bill : James Butler Hickok in war, media, and memory - Ashdown, Paul, 1944-; Caudill, Edward, 1953- (Engaging the Civil War, 2020)
"By investigating the allure and power of Wild Bill Hickok's myth, Ashdown and Caudill explain how American journalism and popular culture have shaped the way Civil War-era figures are remembered and reveal how Americans have embraced violence as entertainment."--